Oil palm diseases and their control practices in Malaysia / Norhaslina Ali - Ali, Norhaslina (Faculty of Plantation and Agrotechnology, 2016)
Oil palm is a very important commodity for many countries especially in Southeast Asia. But there so much concerns about its various pest and diseases around the world. Malaysian oil palm industry has been struggle with the destruction caused by soil borne diseases such as basal stem rot (BSR). There have many diseases can be found in different oil palm growth stages such as in nursery, immature planting and main field plantation. Nevertheless, different oil palm growing countries have their own different of disease incidences occurred in their oil palm plantation area for example BSR mainly found in Southeast Asia. The most serious disease that caused significant losses in oil palm production is the BSR which manifested by fungal Ganoderma boninense. Previously, many studies have been done and reported on different control strategies for BSR on oil palm such as cultural, chemical, biological and etc. The cultural method only has a little effect on the control of BSR but could prolong the life span of infected-oil palm trees. Our review study has highlighted on diverse implementation of control strategies against all main diseases in oil palm plantations in Malaysia. Therefore, we could identify the most significant threat and its possible curative measures to manage the diseases.